Nurse–Patient Connectedness and Nurses' Professional Quality of Life: Experiences of Volunteering at a Pediatric Oncology Camp. (March 2020) - Cherven, Brooke; Jordan, Dorothy; Hale, Sally; Wetzel, Martha; Travers, Curtis; Smith, Kylie
Objective: Pediatric oncology nurses can experience burnout, vicarious traumatization, and compassion fatigue related to the unique stressors of their profession. Opportunities to enhance nurses' professional commitment and nurse–patient connectedness may mitigate these stressors. This study explored the impact of volunteering at a local oncology camp on pediatric oncology nurses' professional quality of life and connectedness with their oncology patients.Method and Sample: Pediatric oncology nurses from a single institution were invited to participate in this mixed methods study. Participants completed a survey assessing professional quality of life, professional commitment, and patient connectedness. Nurses who had oncology camp volunteer experience were invited to participate in a qualitative interview.Results: Compared with noncamp nurses ( n = 23), camp nurses ( n = 25) had increased odds of a low burnout score (odds ratio = 6.74, 95% confidence interval [1.10, 41.43], p = .039) and increased odds of a high compassion satisfaction score (odds ratio = 4.69, 95% confidence interval [1.14, 19.32], p = .033). Qualitative interviews supported the impact of volunteering at camp on nurses' personal and professional perspective, nursing practice, and delivery of person-centered care.Conclusion: Volunteering at a pediatric oncology camp provided nurses the opportunity to engage with patients, share experiences, and view patients as individuals while still maintaining professional boundaries. Nurses who volunteer at camp described a perspective moving beyond patient-centered to person-centered care, and for some pediatric oncology nurses, camp volunteering may be a novel way to mitigate burnout and an important tool to enhance resiliency.